Transient hyperphosphatasemia: Possible association with pediatric acute respiratory infection - Yoshihiko Sakurai; Takafumi Higashiguchi (Wiley, 2021)
ABSTRACT Importance Acute respiratory infections are quite prevalent in children. Transient hyperphosphatasemia (TH) is defined as the transient elevation of serum alkaline phosphatase (ALP) level, which occurs mainly in infants and children without liver or bone disorders. Although no apparent cause has been identified, a possible association of respiratory infections with TH has been reported in the literature. Objective In this study, we aimed to investigate the association between TH and respiratory infectious diseases. Methods We collected the results of biochemical investigations, including ALP level, for a period of 5 years in our hospital. We then examined the patients with transiently elevated ALP levels of > 2000 U/L. Results During the observation period, 1501 blood samples were collected from 1097 patients. Marked elevation of serum ALP level was observed in 12 patients. All patients with hyperphosphatasemia, except for one with Fanconi syndrome attributable to the underlying Wilson's disease, were aged < 5 years and were diagnosed with TH. Ten of these 11 patients with TH had acute respiratory infections. Marked ALP elevation was not found in any patients with non‐inflammatory diseases. ALP isoenzyme profiles showed a characteristic pattern in all six patients in whom the ALP isoenzyme test was conducted. Interpretation Our results suggest an association between respiratory infections and TH. The consideration of TH in patients with acute respiratory infections may lead to earlier and accurate diagnosis of this condition, thereby avoiding unnecessary medical interventions.